Climate change alters the optimal wind-dependent flight routes of an avian migrant. Issue 1854 (3rd May 2017) - Nourani, Elham; Yamaguchi, Noriyuki M.; Higuchi, Hiroyoshi
Abstract : Migratory birds can be adversely affected by climate change as they encounter its geographically uneven impacts in various stages of their life cycle. While a wealth of research is devoted to the impacts of climate change on distribution range and phenology of migratory birds, the indirect effects of climate change on optimal migratory routes and flyways, through changes in air movements, are poorly understood. Here, we predict the influence of climate change on the migratory route of a long-distant migrant using an ensemble of correlative modelling approaches, and present and future atmospheric data obtained from a regional climate model. We show that changes in wind conditions by mid-century will result in a slight shift and reduction in the suitable areas for migration of the study species, the Oriental honey-buzzard, over a critical section of its autumn journey, followed by a complete loss of this section of the traditional route by late century. Our results highlight the need for investigating the consequences of climate change-induced disturbance in wind support for long-distance migratory birds, particularly species that depend on the wind to cross ecological barriers, and those that will be exposed to longer journeys due to future range shifts.